PENGARUH MODEL PEMBELAJARAN KOOPERATIF MURDER TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN INFORMATIKA KELAS X DI SMKN I ENAM LINGKUNG - Hatta, Arif Rahman; Darman, Regina Ade; Nurdin, Bernediv (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2025)
The aim of this research is to determine the influence of the Murder Cooperative Learning Model on Student Learning Outcomes in Class X Informatics Subjects at SMKN 1 Enam Lingkung. This research is quantitative research. The Quasi Experiment method can be interpreted as a research approach used to find the effect of certain treatments on others under controlled conditions. The population of this study were all class X MPLB students at SMKN 1 Enam Lingkung. The research sample was determined using the Cluster Random sampling technique. Data collection techniques include observation, tests and documentation. Data analysis techniques include descriptive tests, normality tests, homogeneity tests, hypothesis tests, normalized gain tests. This research proves that there is a positive and significant influence on the use of the murder cooperative learning model on student learning outcomes in class X informatics subjects at SMKN 1 Enam Lingkung. Based on the results of the Normalized Gain test above, it can be seen that the average N-Gain score for the experimental class is 61.8222 with the highest score being 100.00 and the lowest score being 43.75.